New city structure: Does it come from the past? - Wawrzyniec Zipser (AESOP, 2010)
The spatial structure of cities, especially large ones, has been a challenge for generations of planners and architects. Its complexity causes many difficulties for the very task of its identification, let alone planning and solving spatial problems. The drive to improve, better yet adapt the spatial structure of a city to the needs of its inhabitants has marked the history of cities as long as they have existed. Regardless of the need for security, prestige, beauty or accessibility, the principle goal has always been functional solutions. The spatial structure of cities is determined by many natural and topographical factors, such as rivers, landscapes and natural resources. Other important factors include their position in the settlement hierarchy or the role a specific unit plays or played in the settlement structure (Zipf’s Law). In addition to historic factors, current tendencies, such as the global economic situation and changes in the spatial behaviour of citizens linked to their level of socio-economic development are influencing the spatial structure of cities. Together all these factors require a city-specific approach. A feasible framework which can be fitted in a flexible way to individual cases will make it possible to prevent undesirable or dangerous processes to the natural and social environment.
Book of proceedings: Urban change : The prospect of transformation